Initiation in photoredox C–H functionalization reactions. Is dimsyl anion a key ingredient? - Buden, Maria Eugenia (2017)
Previous studies have reported the arylation of unactivated arenes with ArX, base (KOtBu or NaOtBu), and an organic additive at high temperatures. Recently, we showed that this reaction proceeds in the absence of additives at rt but employs UV-vis light. However, details of mechanisms that can use a photoinduced base-promoted homolytic aromatic substitution reaction (photo-BHAS) have remained elusive until now. This work examines different mechanistic routes of the essential electron-transfer step (ET) of this reaction in order to identify a possible path for the formation of 1-adamantyl radicals from 1-haloadamantanes (initiation step). On the basis of photochemical and photophysical experiments and computational studies, we propose an unprecedented initiation step that could also be applied to other ET reactions performed in DMSO. For the first time, it is reported that dimsyl anion, formed from a strong base and DMSO (solvent), is responsible for inducing the initiation by a photo-BHAS process on alkyl halides.